Copper-based disinfectant composite functional membrane material as well as preparation method and application thereof

By combining CuNPs, ZnIn2S4 and CNTs, a copper-based disinfectant composite functional membrane material was designed. Using photocatalytic and membrane separation technology, the inefficiency and material instability of traditional water disinfection technology were solved, and efficient bacterial disinfection was achieved. disinfecting and self-cleaning functions have good environmental purification potential.

CN119236710AActive Publication Date: 2025-01-03ZHEJIANG UNIV OF TECH +1

Patent Information

Application Number
CN202411783292.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-03
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Traditional water disinfection technology has problems of disinfection by-products, low energy efficiency and high cost, and nanomaterials are prone to oxidation in air or water media, resulting in instability, resulting in material recycling and loss, affecting their application effect.

Method used

A copper-based disinfectant composite functional membrane material was designed. By combining CuNPs, ZnIn2S4 and CNTs, photocatalytic and membrane separation technology, CNTs-PEI/Cu-ZnIn2S4 composite membrane with high-efficiency sterilization and self-cleaning functions were prepared. , photocatalytic generation of ROSs is used for bacterial disinfection, and the adsorption and interception performance of the material is improved through hydrophilic polymer functionalization and vacuum-assisted filtration.

Benefits of technology

It has achieved efficient disinfection of bacteria, reaching an inactivation rate of 100% within 2 hours, high stability of the material, recyclable, self-cleaning and broad-spectrum applicability, and good environmental purification potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236710A_ABST
    Figure CN119236710A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-based sterilizing agent composite functional film material and a preparation method and application thereof, the preparation method comprises the following steps: preparing a sulfur-indium-zinc composite material ZIS by a hydrothermal method, preparing a copper ion solution, mixing the copper ion solution with the composite material, and carrying out a photodeposition reaction to obtain a copper-based sterilizing agent CZIS; the preparation method comprises the following steps: functionalizing acidified carbon nanotubes through polyethyleneimine, and depositing CNTs on a hydrophilic polyvinylidene fluoride film to form a thin film in combination with a vacuum-assisted filtering method; and filtering the CZIS dispersoid on the CNTs-PEI membrane, so as to obtain the copper-based disinfectant composite functional membrane material CNTs-PEI / CZIS. The CNTs-PEI / CZIS composite membrane disclosed by the invention can realize high-efficiency sterilization on bacteria, has the antibacterial ability close to 100% (the bacterial concentration is greater than or equal to 106 CFU / mL) within 2 hours, is high in stability, can be recycled, has self-cleaning and broad-spectrum applicability, has good environment purification potential, and is a multifunctional membrane material integrating high-efficiency sterilization and self-cleaning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of bactericidal composite functional materials, and in particular relates to a copper-based disinfectant composite functional membrane material and a preparation method and application thereof. Background Art

[0002] Water resource security is a major issue concerning human health and social development. Antibiotics are effective drugs for treating bacterial infections, but due to the abuse of antibiotics, more and more bacteria have developed drug resistance, and some bacteria have even acquired multi-drug resistance, resulting in the widespread presence of drug-resistant bacteria in water systems, posing a great threat to human health. Traditional disinfection technologies such as chlorine, ozone and ultraviolet rays have problems such as disinfection by-products, low energy efficiency and high costs. Nanomaterials can achieve bactericidal effects by destroying cell structures and affecting cell metabolism, and have the advantages of high efficiency, safety and long life, and are considered to be the most promising new method in the field of disinfection.

[0003] Copper and copper-based compounds have been known as disinfectants since ancient times. Copper in nanoparticle form (CuNPs) has a larger surface area to volume ratio, increased antibacterial properties, and improved optical properties. However, the instability caused by the easy oxidation of CuNPs in air or water media can cause their loss. Synthetic composites are one of the most effective strategies to solve the problem of metal stability. They can also improve catalytic performance through synergistic effects between components and be applied to environmental disinfection. Ternary sulfide ZnIn 2 S 4 As an advanced functional material, it has excellent chemical stability, visible light absorption performance and good photoelectric conversion performance. It has certain antibacterial properties by generating ROSs through photocatalysis. 2 S 4 As a potential electron donor, photocatalytic in situ reduction of copper ions under visible light irradiation can improve the photogenerated electrons (e - ) and holes (h + ) for the separation efficiency.

[0004] Photocatalytic materials can achieve photocatalytic degradation of bacteria and other pollutants under the drive of visible light irradiation under the appropriate band gap, and also have the characteristics of non-toxicity, stability, and self-cleaning. However, there are problems such as material recovery and material loss in practical applications. Membrane separation technology has become the main way to repair the water environment due to its advantages such as environmental sustainability and energy saving. Combining catalytic materials with membrane separation technology may be one of the powerful means to solve this problem. In the scientific field of constructing multifunctional separation membranes, carbon nanotubes (CNTs) have attracted widespread attention due to their high specific surface area and the ability to functionalize functional groups with specific properties through polymers. Therefore, CuNPs with good antibacterial properties and ZnIn with excellent photocatalytic properties are combined.2 S 4 The combination of CNTs with rich specific surface area and the design of composite functional membrane materials with efficient sterilization and self-cleaning may have good application prospects. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies in the prior art, the purpose of the present invention is to provide a copper-based disinfectant composite functional membrane material and a preparation method and application thereof. The specific technical scheme is as follows: A method for preparing a copper-based disinfectant composite functional membrane material comprises the following steps: 1) Dissolve zinc salt, indium salt and sulfur source in water, adjust the pH of the mixed solution to acidic, transfer the mixed solution to a hydrothermal reactor for reaction; after the reaction is completed, cool to room temperature, centrifuge, wash and dry the precipitate to obtain a sulfur-indium-zinc composite material; 2) Dissolve the copper salt in ultrapure water, ultrasonically disperse the prepared sulfur-indium-zinc composite material in the water, and mix it with the prepared copper ion solution; slowly inject the reducing solution under magnetic stirring and light irradiation, and perform a photodeposition reaction for 5-180 min to obtain a copper-based disinfectant, which is recorded as Cu-ZnIn 2 S 4 ; 3) Place CNTs in H 2 SO 4 / HNO 3 The mixed solution is heated at 40-80°C for 2-6 h; after the acidification, the solution is allowed to stand to remove the supernatant, distilled water is added to the lower solution, and after the solution is allowed to stand for stratification, the supernatant is repeatedly removed and distilled water is added until the supernatant is neutral; the obtained neutral solution is filtered and washed, and the obtained black substance is placed in a vacuum drying oven at 30-80°C and dried overnight to obtain acidified carbon nanotubes, which are recorded as CNTs-COOH. Carbon nanotubes are selected to construct multifunctional separation membranes. On the one hand, it has a high specific surface area, which is conducive to the effective adsorption of bacteria; on the other hand, it can be used as a secondary reaction platform to design functional membranes through chemical crosslinking, interface assembly and nanoparticle modification, thereby improving their ability to capture target bacteria; 4) The acidified carbon nanotubes and polyethyleneimine are ultrasonically dispersed, the mixed solution is centrifuged, the supernatant is removed, the precipitate is washed with ultrapure water for 3 to 5 times, and dried to obtain PEI-functionalized CNTs, which are recorded as CNTs-PEI. The acidified CNTs are functionalized with PEI so that the surface of CNTs-PEI contains hydrophilic amino and carboxyl groups. The improvement of the hydrophilicity of the membrane promotes the kinetic effect between the membrane surface and the microorganisms and the effect of adsorption and mass transfer, improves the adsorption and interception performance of bacteria, and thus promotes the disinfection effect on bacteria; 5) preparing the CNTs-PEI obtained in step 4) into a CNTs-PEI dispersion; filtering the CNTs-PEI dispersion onto a hydrophilic polyvinylidene fluoride membrane at 0.9 bar using a vacuum-assisted filtration method to obtain a CNTs-PEI membrane; and depositing carbon nanotubes on the hydrophilic polyvinylidene fluoride (PVDF) membrane to form a thin film using a vacuum-assisted filtration method; 6) Preparation of Cu-ZnIn 2 S 4 Dispersion, Cu-ZnIn was filtered on the CNTs-PEI membrane prepared in step 5). 2 S 4 Dispersion, obtain CNTs-PEI / Cu-ZnIn 2 S 4 Composite membrane.

[0006] Furthermore, the zinc salt in step 1) is zinc nitrate, zinc sulfate, zinc chloride, zinc phosphate, zinc acetate, zinc citrate, zinc isooctanoate or zinc glycinate, the indium salt is indium nitrate, indium sulfate, indium chloride, indium phosphate, indium acetate or indium citrate, and the sulfur source is thioacetamide, thiourea, ammonium sulfide or sodium thiosulfate. The molar ratio of the zinc salt, indium salt and sulfur source is 2-3:4-6:8-12.

[0007] Furthermore, the copper salt in step 2) is copper nitrate, copper phosphate, copper chloride, copper acetate or sodium copper ethylenediaminetetraacetate, and the mass ratio of copper to sulfur-zinc-indium material is 0.1-2:10.

[0008] Furthermore, the reducing solution in step 2) is sodium borohydride, potassium borohydride, hydrazine, ethanol, ammonia water or sodium sulfite, the concentration of the reducing solution is 0.01-0.6 mol / L, the molar ratio with the copper salt is 3-15:1, and the injection speed of the reducing solution is 2-3 drops per second.

[0009] Furthermore, in step 3) acidification of carbon nanotubes, 95-98% H 2 SO 4 With 70% HNO 3 The volume ratio is 3:1.

[0010] Furthermore, in step 4), the mass ratio of the acidified carbon nanotubes to polyethyleneimine is 0.5-2:10; the mixed solution is ultrasonically dispersed for 0.5-1 h and centrifuged at 5000-10000 r / min for 3-10 min, the supernatant is removed, and the precipitate is washed with ultrapure water for 3-5 times and dried at 30-80°C.

[0011] Furthermore, in step 5), the ratio of the mass of CNTs-PEI filtered onto the polyvinylidene fluoride membrane to the membrane area is 1-4:8, with the mass unit being g and the area unit being m 2, the concentration of CNTs-PEI dispersion is 80-120 mg / L.

[0012] Furthermore, in step 6), the ratio of the mass of Cu-ZIS filtered onto the CNTs-PEI membrane to the membrane area is 1-4:4, with the mass unit being g and the area unit being m 2 , the concentration of Cu-ZIS dispersion is 60-120 mg / L.

[0013] A copper-based disinfectant composite functional membrane material prepared by the above-mentioned preparation method.

[0014] The application of the copper-based disinfectant composite functional membrane material in the photocatalytic antibacterial process, in which the CNTs-PEI / CZIS composite membrane with good hydrophilicity can effectively promote its interaction with bacteria and achieve more effective bacterial disinfecting, such as Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and miscellaneous bacteria in actual water samples, can reach a 100% inactivation rate in 2 hours (bacterial concentration ≥10 6 CFU / mL); The CNTs-PEI / CZIS composite membrane has high stability, is recyclable, self-cleaning and has broad-spectrum applicability. It has good environmental purification potential and is a composite functional membrane material that integrates high-efficiency sterilization and self-cleaning.

[0015] The beneficial effects of the present invention are: 1) A series of CNTs-PEI / CZIS composite membranes were designed and prepared by using hydrophilic polymer functionalization and vacuum-assisted filtration. The acidified CNTs were functionalized with PEI, so that the surface of CNTs-PEI contained hydrophilic amino and carboxyl groups, which had a high affinity for water and could adsorb and intercept bacteria on the membrane surface. Under the irradiation of visible light, the ROSs produced by ZIS could directly induce the oxidation of cell components, destroy the bacterial cell wall, and lead to bacterial inactivation. The addition of Cu brought more active sites, which was conducive to accelerating the inactivation of bacteria, generating more ROSs, and further increasing the e - Used for the reduction of Cu, extending the service life of the material.

[0016] 2) CNTs-PEI / CZIS composite membrane can achieve high efficiency in disinfecting bacteria, with the antibacterial capacity close to 100% within 2 hours (bacterial concentration ≥ 10 6 CFU / mL), through circulation experiments and bactericidal performance experiments on different bacteria, it was further demonstrated that the composite membrane has good chemical adaptability, high stability, recyclability, self-cleaning and broad-spectrum applicability, and has good environmental purification potential, which can provide new methods and new ideas for the effective treatment of wastewater containing harmful microorganisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 XRD spectra of CNTs-PEI, CNTs-PEI / ZIS and CNTs-PEI / CZIS-25 composite films prepared in Example 1; Figure 2 This is the EDS element distribution diagram of CZIS prepared in Example 1; Figure 3 Comparison of the photocatalytic antibacterial effects of CNTs-PEI, CNTs-PEI*, CNTs-PEI / ZIS, CNTs-PEI / CZIS-15, CNTs-PEI / CZIS-25, and CNTs-PEI / CZIS-30 composite films; Figure 4 This is a comparison chart of the effects of the CNTs-PEI / CZIS-25 composite membrane of the present invention on catalytic disinfecting of Pseudomonas aeruginosa, Staphylococcus aureus and natural water bacteria; Figure 5 This is a graph showing the cyclic sterilization efficiency of the CNTs-PEI / CZIS-25 composite membrane of the present invention. DETAILED DESCRIPTION

[0018] The present invention is further described below in conjunction with the embodiments and the accompanying drawings, but the protection scope of the present invention is not limited thereto.

[0019] Example 1 Preparation of CNTs-PEI / CZIS composite functional membrane material

[0020] Preparation of CNTs-PEI / CZIS composite functional membrane materials: 1) CNTs were mixed with 95-98% H 2 SO 4 / 70%HNO 3 The mixed solution was heated at 70 °C for 2 h; after the acidification, the solution was allowed to stand and the supernatant was removed, and distilled water was added to the lower solution. After the solution was allowed to stand and stratified, the supernatant was removed repeatedly and distilled water was added until the supernatant was neutral; the obtained neutral solution was filtered and washed to remove impurities; the black substance obtained by filtration was placed in a vacuum drying oven at 40 °C and dried overnight to obtain acidified carbon nanotubes, which were recorded as CNTs-COOH; 2) Dissolve 0.02 g of acidified carbon nanotubes (CNTs-COOH) and 0.2 g of polyethyleneimine (PEI) in 200 mL of ultrapure water and disperse them by ultrasonication for 1 h; centrifuge the mixed solution at 8000 r / min for 10 min, remove the supernatant, wash the precipitate with ultrapure water for 3 times, and dry it at 30 °C to obtain PEI-functionalized CNTs, which are recorded as CNTs-PEI; 3) Prepare CNTs-PEI into a 100 mg / L CNTs-PEI dispersion; filter 10 mL of the dispersion at 0.9 bar to a membrane area of ​​40 cm 2 On polyvinylidene fluoride (PVDF) membrane, CNTs-PEI membrane was obtained; 4) Preparation of Cu-ZnIn 2 S 4 dispersion (100 mg / L), set aside; 40 cm 2 Different volumes of Cu-ZIS dispersion (15 mL, 25 mL, and 30 mL) were filtered on the CNTs-PEI membrane to obtain CNTs-PEI / Cu-ZnIn 2 S 4 Composite membranes and labeled with CNTs-PEI / CZIS-x, where x represents Cu-ZnIn 2 S 4 Similarly, CNTs-PEI / ZIS composite membranes (without Cu) were prepared according to the same preparation process and operating conditions of CNTs-PEI / CZIS composite membranes, and the concentration and volume of ZIS dispersion were the same as those of CZIS-25.

[0021] ZnIn 2 S 4 Preparation of materials: 0.068 g ZnCl 2 , 0.239 g InCl 2 ·4H 2 O and 0.15 g CH 3 CSNH 2 Dissolve in an appropriate amount of ultrapure water, mix evenly, adjust the pH of the mixed solution to 1.0 with 2 M HCl solution, stir magnetically for 30 min, and form 40 mL of mixed metal salt solution; transfer the mixed solution to a hydrothermal reactor with a polytetrafluoroethylene liner; seal the hydrothermal reactor and put it in an oven, and keep it warm at 160 °C for 16 h; after the reaction is completed, wait for the precipitate to cool to room temperature, centrifuge and wash it several times with ultrapure water and anhydrous ethanol to obtain a dark yellow solid substance, which is placed in a vacuum oven at 60 °C and vacuum dried for 12 h to obtain ZnIn 2 S 4 Material.

[0022] Cu-ZnIn 2 S 4 Preparation of materials: 4.2 mg CuCl 2 Ultrasonic dissolution was performed in 5 mL of ultrapure water to prepare a copper ion solution for later use; 14.3 mg NaBH4 Ultrasonic dissolution in 5 mL ultrapure water to prepare a sodium borohydride aqueous solution for use; 100 mg of the prepared ZnIn 2 S 4 The material was ultrasonically dispersed in 40 mL of water, mixed with the prepared copper ion solution, and then transferred into a quartz photoreactor after ultrasonic treatment. Nitrogen was bubbled to remove dissolved oxygen. Under magnetic stirring and illumination, sodium borohydride aqueous solution was injected at a rate of 3 drops per second. The photodeposition reaction was completed after 60 minutes, and the room temperature was maintained in a constant temperature water bath during the reaction. After the reaction, ultrapure water and anhydrous ethanol were used for centrifugal washing to remove residual salt, and the mixture was dried in a vacuum oven at 60°C for 12 hours to obtain Cu-ZnIn 2 S 4 Material.

[0023] The XRD spectra of the CNTs-PEI, CNTs-PEI / ZIS and CNTs-PEI / CZIS-25 composite films prepared in Example 1 are shown in Figure 1 As shown, the prepared CNTs-PEI material has obvious standard diffraction peaks of carbon-based materials, corresponding to the (002) and (110) crystal planes of carbon materials. In the XRD spectra of CNTs-PEI / ZIS and CNTs-PEI / CZIS-25 composite films, the characteristic diffraction peaks of Cu are not obvious due to the low loading amount, and the characteristic diffraction peaks of ZIS can be clearly observed, corresponding to the (006), (102), (110) and (116) crystal planes of hexagonal ZIS (JCPDS No.72-0773), indicating that CZIS and CNTs-PEI have been successfully composited. The EDS element distribution corresponding to CZIS is shown in Figure 1. Figure 2 As shown, Zn, In, S, and Cu elements are evenly distributed, which indicates that Cu is evenly distributed on the ZIS.

[0024] Example 2 CNTs-PEI / CZIS-25 composite functional membrane material is used to disinfect Escherichia coli

[0025] The photocatalytic antibacterial experiment evaluated the antibacterial properties of various composite membrane materials by disinfecting bacteria. The disinfection steps were as follows: 200 μL of Escherichia coli suspension was added to a conical flask (sterilized at high temperature) containing 10 mL of sterile Tryptic Soy Broth (TSB) broth; they were transferred to a shaker and cultured at 37 °C, 100 rpm for 12 h; the cut CNTs-PEI / CZIS-25 composite membrane samples were placed in a 24-well culture plate and 0.1 mL of bacterial suspension (10 6 CFU mL -1) and 1 mL of PBS solution sterilized by high temperature; during the photocatalytic process (xenon lamp, 420<λ<630 nm, 300 W), 0.1 mL of the suspension was taken every 1 h, and the bacterial sample was diluted by the standard serial dilution method; 0.1 mL of the diluted bacterial sample was dropped onto the TSA medium, and spread evenly with an L-shaped spreading stick, placed in a bacterial incubator at 37 °C for 18 h, and the colonies on the agar plate were counted. Figure 3 It can be seen that after 2 h, the inactivation rate of E. coli by the CNTs-PEI / CZIS-25 composite membrane material disinfection system can be close to 100%. This excellent performance comes from ZIS, which is reflected in the hydrophilic amino and carboxyl groups on the surface of the CNTs-PEI / CZIS-25 composite membrane, which can adsorb and intercept bacteria on the surface. Under the irradiation of visible light, the ROSs generated by ZIS, such as HO• and O2• - , can directly induce the oxidation of cell components, destroy bacterial cell walls, and cause active substances to leak from the inside of cells, leading to bacterial inactivation. On the other hand, the excellent antibacterial properties of Cu itself and its "special properties". The addition of Cu not only brings more active sites, which is conducive to accelerating the inactivation of bacteria, but also can inhibit e - / h + Compound, generate more ROSs, and further - Used for the reduction of Cu and to extend the service life of the material.

[0026] Comparative Example 1 CNTs-PEI membrane material is used to disinfect Escherichia coli

[0027] The CNTs-PEI membrane material used is from Example 1. Referring to the photocatalytic antibacterial process of Example 2, Escherichia coli was selected as the object of evaluation for disinfecting. Figure 3 It can be seen that after 2 h, the inactivation effect of the CNTs-PEI membrane material disinfection system on Escherichia coli was weak, with an inactivation rate of only 35%, indicating that under the irradiation of visible light, the acidified carbon nanotubes were functionalized with PEI, which may cause mechanical damage to the cell wall or cell membrane of some bacteria.

[0028] Comparative Example 2: CNTs-PEI* membrane material is used to disinfect Escherichia coli

[0029] The CNTs-PEI material used was from Example 1. Using vacuum assisted filtration, 15 mL of 100 mg / L CNTs-PEI in step 3) of Example 1 was filtered at 0.9 bar to a volume with an effective area of ​​40 cm 2 On the polyvinylidene fluoride (PVDF) membrane, a CNTs-PEI* membrane was obtained. Referring to the photocatalytic antibacterial process of Example 2, Escherichia coli was selected as the object of disinfection evaluation. Figure 3It can be seen that after 2 h, the inactivation rate of Escherichia coli by CNTs-PEI* membrane material was 38%, which was not significantly different from the sterilization effect of CNTs-PEI membrane material. This shows that in this elimination system, the addition amount of CNTs-PEI dispersion has little effect on the bactericidal effect, and mechanical damage to bacteria may be the main sterilization method of CNTs-PEI dispersion.

[0030] Comparative Example 3 CNTs-PEI / ZIS composite functional membrane material is used to disinfect Escherichia coli

[0031] The CNTs-PEI / ZIS composite film material used is from Example 1. Referring to the photocatalytic antibacterial process of Example 2, Escherichia coli was selected as the object of evaluation for disinfecting. Figure 3 It can be seen that after ZIS modification, the inactivation rate of Escherichia coli by the CNTs-PEI / ZIS composite film material disinfection system was close to 75% after 2 h. This significant change was attributed to the visible light absorption ability of ZIS in the visible spectrum range.

[0032] Comparative Example 4: Use of CNTs-PEI / CZIS-15 and CNTs-PEI / CZIS-30 composite functional membrane materials to disinfect Escherichia coli

[0033] The CNTs-PEI / CZIS-15 and CNTs-PEI / CZIS-30 composite membrane materials used are from Example 1. Referring to the photocatalytic antibacterial process of Example 2, Escherichia coli was selected as the object of evaluation for disinfecting. Figure 3 It can be seen that after 2 hours, the inactivation rate of E. coli by the CNTs-PEI / CZIS-15 composite membrane material disinfection system is close to 90%, and the inactivation rate of E. coli by the CNTs-PEI / CZIS-30 composite membrane material disinfection system is close to 100%. From the sterilization effects of CNTs-PEI / CZIS-15, CNTs-PEI / CZIS-25, and CNTs-PEI / CZIS-30 composite membrane materials, it can be seen that the CNTs-PEI / CZIS-15 composite membrane material failed to completely inactivate E. coli, considering that it is because of Cu-ZnIn 2 S 4 The amount of dispersion added was small, and a small amount of E. coli survived. The sterilization effects of CNTs-PEI / CZIS-25 and CNTs-PEI / CZIS-30 composite membrane materials were almost the same, indicating that 25 mL of Cu-ZnIn 2 S 4 The dispersion is sufficient to achieve optimal sterilization effect.

[0034] Example 3 CNTs-PEI / CZIS-25 composite functional membrane material is used to disinfect Pseudomonas aeruginosa

[0035] The CNTs-PEI / CZIS-25 composite film material used is from Example 1. Referring to the photocatalytic antibacterial process of Example 2, Pseudomonas aeruginosa was selected as the object of disinfection evaluation. Figure 4 It can be seen that after 2 h, the inactivation rate of Pseudomonas aeruginosa by the CNTs-PEI / CZIS-25 composite membrane material disinfection system can be close to 100%.

[0036] Example 4 CNTs-PEI / CZIS-25 composite functional membrane material is used to disinfect Staphylococcus aureus

[0037] The CNTs-PEI / CZIS-25 composite film material used is from Example 1. Referring to the photocatalytic antibacterial process of Example 2, Staphylococcus aureus was selected as the disinfection evaluation object. Figure 4 It can be seen that after 2 h, the inactivation rate of Staphylococcus aureus by the CNTs-PEI / CZIS-25 composite membrane material disinfection system was also close to 100%.

[0038] Example 5 Application of CNTs-PEI / CZIS-25 composite functional membrane material in natural water sterilization

[0039] The CNTs-PEI / CZIS-25 composite membrane material used is from Example 1. Referring to the photocatalytic antibacterial process of Example 2, natural water bodies are selected as the disinfection evaluation object. Figure 4 It can be seen that after 1 h, the inactivation rate of the CNTs-PEI / CZIS-25 composite membrane material disinfection system on natural water bacteria is also close to 100%.

[0040] Example 6 Cyclic sterilization performance of CNTs-PEI / CZIS-25 composite functional membrane material

[0041] The CNTs-PEI / CZIS-25 composite membrane material used is from Example 1. Referring to the photocatalytic antibacterial process of Example 2, Escherichia coli was selected as the object of disinfection evaluation. In order to investigate the cyclic performance of the CNTs-PEI / CZIS-25 composite membrane material, 5 cyclic sterilization experiments were carried out on it. After each experiment, the used composite membrane was recovered by alternating alcohol / water washing and visible light irradiation (self-cleaning). The cyclic sterilization effect of the CNTs-PEI / CZIS-25 composite membrane is shown in the figure. Figure 5 As shown in the figure, it can be clearly observed that the bactericidal efficiency after the cycle remains at a high level (after five cycles, E. coilThe sterilization efficiency was still maintained above 98%). This indicates that the prepared CNTs-PEI / CZIS-25 composite membrane has high stability and can be effectively reused. At the same time, it can be driven by visible light for disinfection and self-cleaning, and has good environmental purification potential.

Claims

1. A method for preparing a copper-based disinfectant composite functional membrane material, characterized in that: The following steps are involved: 1) Dissolve zinc salt, indium salt and sulfur source in water, adjust the pH of the mixed solution to acidic, transfer the mixed solution to a hydrothermal reactor for reaction; after the reaction is completed, cool to room temperature, centrifuge, wash and dry the precipitate to obtain a sulfur-indium-zinc composite material; 2) dissolving the copper salt in ultrapure water, ultrasonically dispersing the prepared sulfur-indium-zinc composite material in the water, and mixing it with the prepared copper ion solution; injecting a reducing solution under magnetic stirring and light irradiation, and performing a photodeposition reaction for 5-180 min to obtain a copper-based disinfectant, which is recorded as Cu-ZnIn2S4; 3) Heat CNTs in a H2SO4 / HNO3 mixed solution at 40-80℃ for 2-6 h; after acidification, let the solution stand and remove the supernatant, add distilled water to the lower solution, let the solution stand and separate, repeatedly remove the supernatant and add distilled water until the supernatant is neutral; filter and wash the obtained neutral solution, and dry the obtained black substance in a vacuum drying oven at 30-80℃ overnight to obtain acidified carbon nanotubes, recorded as CNTs-COOH; 4) Ultrasonic dispersion of the acidified carbon nanotubes and polyethyleneimine, centrifugation of the mixed solution, removal of the supernatant, washing the precipitate with ultrapure water for 3 to 5 times, and drying to obtain PEI-functionalized CNTs, recorded as CNTs-PEI; 5) preparing the CNTs-PEI obtained in step 4) into a CNTs-PEI dispersion; filtering the dispersion onto a hydrophilic polyvinylidene fluoride membrane at 0.9 bar using a vacuum-assisted filtration method to obtain a CNTs-PEI membrane; 6) preparing a Cu-ZnIn2S4 dispersion, filtering the Cu-ZnIn2S4 dispersion on the CNTs-PEI membrane prepared in step 5) to obtain a CNTs-PEI / Cu-ZnIn2S4 composite membrane.

2. The method for preparing a copper-based disinfectant composite functional membrane material according to claim 1, characterized in that: The zinc salt in step 1) is zinc nitrate, zinc sulfate, zinc chloride, zinc phosphate, zinc acetate, zinc citrate, zinc isooctanoate or zinc glycinate, the indium salt is indium nitrate, indium sulfate, indium chloride, indium phosphate, indium acetate or indium citrate, the sulfur source is thioacetamide, thiourea, ammonium sulfide or sodium thiosulfate, and the molar ratio of the zinc salt, indium salt and sulfur source is 2-3:4-6:8-12.

3. The method for preparing a copper-based disinfectant composite functional membrane material according to claim 1, characterized in that: The copper salt in step 2) is copper nitrate, copper phosphate, copper chloride, copper acetate or sodium copper ethylenediaminetetraacetate, and the mass ratio of copper to the sulfur-indium-zinc composite material is 0.1-2:

10.

4. The method for preparing a copper-based disinfectant composite functional membrane material according to claim 1, characterized in that: The reducing solution in step 2) is sodium borohydride, potassium borohydride, hydrazine, ethanol, ammonia water or sodium sulfite, the concentration of the reducing solution is 0.01-0.6 mol / L, the molar ratio of the reducing solution to the copper salt is 3-15:1, and the injection speed of the reducing solution is 2-3 drops per second.

5. The method for preparing a copper-based disinfectant composite functional membrane material according to claim 1, characterized in that: Step 3) During the acidification of carbon nanotubes, the volume ratio of 95-98% H2SO4 and 70% HNO3 is 3:

1.

6. The method for preparing a copper-based disinfectant composite functional membrane material according to claim 1, characterized in that: In step 4), the mass ratio of the acidified carbon nanotubes to polyethyleneimine is 0.5-2:10; ultrasonic dispersion is performed for 0.5-1 h, the mixed solution is centrifuged at 5000-10000 r / min for 3-10 min, the supernatant is removed, the precipitate is washed with ultrapure water for 3-5 times, and dried at 30-80°C.

7. The method for preparing a copper-based disinfectant composite functional membrane material according to claim 1, characterized in that: The ratio of the mass of CNTs-PEI filtered onto the polyvinylidene fluoride membrane to the membrane area in step 5) is 1-4:8, with the mass unit being g and the area unit being m 2 , the concentration of CNTs-PEI dispersion is 80-120 mg / L.

8. The method for preparing a copper-based disinfectant composite functional membrane material according to claim 1, characterized in that: The ratio of the mass of Cu-ZIS filtered onto the CNTs-PEI membrane to the membrane area in step 6) is 1-4:4, with the mass unit being g and the area unit being m 2 , the concentration of Cu-ZIS dispersion is 60-120 mg / L.

9. A copper-based disinfectant composite functional membrane material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the copper-based disinfectant composite functional membrane material as claimed in claim 9 in a photocatalytic antibacterial process.

Citation Information

Patent Citations

  • Hydrophilic grafted multiwalled carbon nanotube modified polyvinylidene fluoride film and preparation method thereof

    CN103785304A

  • Preparation method of in-situ quaternized antibacterial agent on surface of carbon nano tube

    CN106118198A

  • Porous photo-thermal membrane having antibacterial performance and preparation method and application thereof

    CN109265717A

  • Copper particle loaded sulfur zinc indium composite material and preparation method and application thereof

    CN115739119A

  • Ocean reinforced concrete piece with anticorrosive function of disinfecting

    CN207193178U

Cited By

  • Carbon-based self-cleaning membrane material for efficiently separating oil-water emulsion as well as preparation method and application of carbon-based self-cleaning membrane material

    CN119281143A

  • A carbon-based self-cleaning membrane material for efficient separation of oil-water emulsions, its preparation method and application

    CN119281143B